Analisis soal higher order thinking skill (HOTS) pembelajaran IPS kelas IV di sekolah dasar - Fitri Istighfar Rini; Sri Marmoah; Sularmi Sularmi (Universitas Sebelas Maret, 2021)
The purpose of this research is to explain the suitability between problem and concept of HOTS in question of social sciences semester 1 of grade fourth Elementary School Kerten 2 Surakarta for the 2020/2021 academic year. This research uses thinking level and stimulus indicators. The results of this research shows that there is no conformity between hots concept and problem because the percentage of HOTS on social science questions only 9%. The primary data in this research is a document evaluate of the learning results of theme 1 to theme 5 social sciences grade fourth Elementary School Kerten 2 Surakarta. The results of this research is useful to improve teachers quality when make a question with cognitive levels to learners so they can make some levels on their assessements. In addition, this research is intend as an option to determine the criteria of the questions to improve the critical thinking of learners.